Escaping the Westphalian Trap: Unionism and Equality in China, Mexico and the United States - Michael J. Zimmer (Revista Latinoamericana de Derecho Social)
With increased economic globalization since the 1980s has come increased economic inequality and a decline in union density in most countries of the world, with one notable exception being the Peoples Republic of China. The decline in unionism contributes to increased inequality. This paper will try to begin to answer the question whether a revived unionism operating transnationally can do to help reduce inequality as it did during the industrial era following World War II. To do that, this paper will compare and contrast the union movements in China, Mexico and the U.S. Part I will set out the contours of the problems the union movement faces because many employers have been able to organize themselves to escape national labor laws and national labor unions. Unions, in these three countries as well as elsewhere, have not escaped the trap set up by the Westphalian-based system of sovereign nation states which use national law to regulate national economies. Part II will sketch out some of the ways the union movement might attempt to respond to the present situation, as well as some of the obstacles such action will need to overcome if the union movement is to escape the Westphalian trap.